1989
DOI: 10.1002/ana.410260511
|View full text |Cite
|
Sign up to set email alerts
|

Microtubular reorganization and dendritic growth response in alzheimer's disease

Abstract: Cytoskeletal disruption is a key pathological feature of Alzheimer's disease (AD). We used refined immunocytochemical techniques to define the range of abnormalities affecting the microtubule system in AD hippocampus. Minimal tau and tubulin immunoreactivity was granular and accumulated in otherwise normal neuronal perikarya. As tau-reactive neurofibrillary tangles formed, granular tau and tubulin staining diminished, and ubiquitin reactivity developed. In regions of high neurofibrillary tangle density, microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(73 citation statements)
references
References 56 publications
7
64
2
Order By: Relevance
“…These factors may then initiate a cascade of events leading to plaque/tangle generation and neurodegeneration. These include the appearance of apoptotic and mitotic markers in "pre-tangle" neurons [155][156][157] and the activation of developmentassociated signal transduction pathways resulting in aberrant cellular changes normally associated with development, such as neuropil thread formation [17,19,241,242]. Tau kinases such as CDK5, GSK3β and Mark1 normally play critical roles in cell cycle control, establishment of neuronal polarity and axonal outgrowth [243][244][245][246], so their roles in tau toxicity may therefore be due to aberrant activation of these same functions during the course of AD pathogenesis [147,[247][248][249] 3b Dendritic tau accumulation leads to tau secretion via multiple mechanisms…”
Section: Predisposing Risk Factors To the Development Of Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may then initiate a cascade of events leading to plaque/tangle generation and neurodegeneration. These include the appearance of apoptotic and mitotic markers in "pre-tangle" neurons [155][156][157] and the activation of developmentassociated signal transduction pathways resulting in aberrant cellular changes normally associated with development, such as neuropil thread formation [17,19,241,242]. Tau kinases such as CDK5, GSK3β and Mark1 normally play critical roles in cell cycle control, establishment of neuronal polarity and axonal outgrowth [243][244][245][246], so their roles in tau toxicity may therefore be due to aberrant activation of these same functions during the course of AD pathogenesis [147,[247][248][249] 3b Dendritic tau accumulation leads to tau secretion via multiple mechanisms…”
Section: Predisposing Risk Factors To the Development Of Loadmentioning
confidence: 99%
“…It was not until the mid 1980s that it became clear that most cases of senile dementia (i.e. "senility") were neurologically indistinguishable from AD, prompting a detailed molecular characterization of the main component proteins of SP (β-amyloid or Aβ) [13] and NFT (tau) [14][15][16][17][18][19], which in turn quickly focused attention on the genetics, biogenesis, function and potential neurotoxicity of these agents. This was particularly true of Aβ and its generation via the proteolytic cleavage of its parent protein (amyloid precursor protein or APP) [20].…”
Section: Introduction / Historical Perspectivementioning
confidence: 99%
“…Also, in the hippocampus, there is a progressive loss of dendritic spines from pyramidal neurons in AD (el Hachimi and Foncin, 1990;Ferrer and Gullotta, 1990). In addition to the loss of synapses, the dendrites of affected neurons in AD show a dystrophic pattern and an accumulation of phosphorylated tau epitopes (McKee et al, 1989;Kowall and McKee, 1993;Su et al, 1994a). By determining spine density and spine morphology of tau-expressing neurons, we demonstrated that PHP tau expression does not induce major alterations in dendritic spines of the infected neurons at the conditions in which neuronal degeneration was evident in the hippocampal slices.…”
Section: Imaging and Evaluation Of Synaptic Morphologymentioning
confidence: 99%
“…Endocytosed proteins that bind to the membrane via charge-charge interactions will undergo an acidification of www.intechopen.com their environment that may favor templating interactions and oligomer formation (67) Hyperphosphorylation, cleavage and aggregation of wild type tau isoforms can be induced simply by increasing the concentration of protein that is not MT-associated and thus vulnerable to misfolding (reviewed by 13,203), causing the release of tau to the cytosol. This kind of release likely accompanies Abeta or axotomy-induced MT loss (32,101), and thus could account for some of the dependence of tau misprocessing on Abeta generation and traumatic head injury in AD (151,178). While aggregate formation is a central event in the misprocessing of aggregation-prone proteins that drive AAND pathogenesis, it remains unclear how it is connected to the diversion of these proteins into the unconventional secretion pathways that might account for the interneuronal transmission of neurofibrillary lesions that appears to occur in these diseases.…”
Section: General Molecular and Cellular Considerationsmentioning
confidence: 99%
“…Interestingly, tau induced neuropathology in tauopathy models produces a number of toxic changes in the dendrites that might shed light on the link between tau misprocessing and interneuronal tau transfer. Tau expression in models causes progressive dendritic degeneration (101) and has specific effects on dendritic MT number (103) and function (61) that resemble both AD pathology (27,151) and the effects of proximal axotomy (72, 182 , 200, 101). A recent result of particular interest in this context is the recent demonstration by Ittner and co-workers (117) that ectopically localized dendritic tau mediates Abeta toxicity in a transgenic mouse tauopathy model.…”
Section: Is Polarity Loss Connected To the Misprocessing And Secretiomentioning
confidence: 99%